Produção de mudas de amburana cearensis (allemao) a.c smith em diferentes substratos irrigada com efluente industrial - Alves, Lívia Laiane Barbosa (Universidade Federal Rural do Semi-Árido, 2019)
Although plentiful on planet earth, in recent decades water-related problems have been intensified, especially in semi-arid regions. Due to the need to produce seedlings for different purposes, the quality of the water for irrigation of the plants can in some cases jeopardize the production, so one of the main alternatives to supply the demand in these places is the reuse of water. The objective of this work was to evaluate the growth of the species Amburana cearensis on different substrates using effluent from a cleaning products industry. The study was carried out in a greenhouse at the Department of Agronomic and Forest Sciences, Federal Rural University of the Semi-Arid (UFERSA), Mossoró-RN. The experiment was conducted in randomized blocks, in a 2 x 5 factorial scheme, corresponding to two substrates and five doses of effluent (0%, 25%, 50%, 75% and 100%). The substrates used were: soil and organic compound (S1); soil and fiber of aguapés (S2). Chemical and toxic metal analyzes were performed on the effluent before the start of the experiment. For the substrates the same analyzes were performed before the beginning and after the end of the experiment. The growth was evaluated by the diameter of the stem (DC) and height of the seedling (H), and the evaluations were performed every 15 days. Absolute growth rates (TCA) and relative growth rates (TCR) were determined. The results of the evaluated characteristics were submitted to analysis of variance and for the qualitative factors was done analysis of average by the test of Tukey to 5% of probability. For the quantitative factors, a regression and correlation analysis was performed. It was verified that the diameter of the mean stem was higher for plants grown in S2 and the mean height was higher in S1. The TCR for plant height and for stem diameter had the same pattern of behavior in the control treatment, and at 25 and 50% doses in S1. In S2, the diameter TCR reduced continuously during the 90 days at all doses. The relative growth rates for height showed a trend of independent reduction of treatments. PH and electrical conductivity were higher in S2. The toxic metals were recorded at low concentrations on substrates and plants. Thus, the seedlings showed good growth characteristics for all treatments, and the 50% dose in S1 achieved the best results for height and diameter
Keywords: Reuso de água; cumaru; taxas de crescimento; aguapé; Water reuse; cumaru; growth rates; Water hyacinth; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE